Maternal arsenic exposure and DNA damage biomarkers, and the associations with birth outcomes in a general population from Taiwan. - Wei-Chun Chou (Public Library of Science (PLoS), 2014)
Inorganic arsenic (iAs) is an established transplacental agent known to affect fetal development in animal studies. However, iAs has not been adequately studied in the general population with respect to iAs exposure during pregnancy and its impact on the health status of newborns. The aims of this study were to 1) elucidate the association between arsenic exposure and oxidative/methylated DNA damage in pregnant women, and 2) determine the association with birth outcomes. A birth cohort study of 299 pregnant mother-newborn pairs was recruited during 2001-2002 in Taiwan. We collected maternal urine samples during the 3(rd) trimester for measuring iAs and its metabolites. We used high-performance liquid chromatography/inductively coupled plasma mass spectrometry (HPLC-ICP-MS) for quantifications of the arsenic species. Liquid chromatography/tandem mass spectrometer (LC-MS/MS) was used to measure the 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) and N(7)-methylguanosine (N(7)-MeG) DNA damage biomarkers. Birth outcomes were collected to assess the associations with maternal arsenic exposure and the DNA damage biomarkers. Multiple regression analyses showed that maternal urinary iAs had positive associations with the methylated N(7)-MeG (beta = 0.35, p<0.001) and oxidative 8-oxodG (beta = 0.24, p<0.001) DNA damage biomarkers, and a decreased one-minute (1-min) Apgar score (beta = -0.23, p = 0.041). Maternal N(7)-MeG was also associated with a decreased 1-min Apgar score (beta = -0.25, p = 0.042). Mutual adjustment for iAs and N(7)-MeG showed an independent and significant prediction for a decreased 1-min Apgar score of iAs (beta = -0.28, p = 0.036). Maternal iAs exposure was associated with both maternal DNA damage and adverse newborn health. Maternal N(7)-MeG levels might be a novel biomarker for monitoring fetal health related to iAs.